Tajemnica miłości Bożej w myśli Franciszka Sawickiego - Mróz, Mirosław (Verbum Vitae, 2013)
Rev. Franciszek Sawicki (1877-1952) was a philosopher, apologist and theologian who thoroughly studied the subject of “God’s eternal love”. Assuming that the most elevated expression for describing God are the words “God is love” (1 J 4:8), Sawicki searched for the most appropriate way to express this truth. He worked in the field of philosophy, theology, and direct life experience. His most significant publications on the subject of God’s love are Filozofia miłości (1924), Bóg jest miłością, Caritas w oświetleniu społecznym i moralno-religijnym (1949). According to Sawicki, man’s life consists not only of a natural dimension (what a man is) but also of his personal life (who a man is). The level of “personality” (the notion used by F. Sawicki) includes both the world of sensual nature, as well as the spiritual dimension of personality, where selfdetermination and responsibility play a special role. Here man’s social and relational assignment should be stressed. It is on the basis of “the ideal of personality” that Sawicki builds up his relational concept of love. It touches upon the intellectual, emotional, and experiential sphere. God, who is Love himself, gave a man power and enabled him to enter into a relationship of love with his Creator and Saviour. It is “the eternal love of God” that provides daily bread and grants his grace resulting from his wisdom and mercy. Sawicki spots the “gesture” of mercy in the commandment of love, which helps man to decide freely about the subject of his love: God, and, through Him and in Him, another man, his neighbour. God’s mercy is particularly emphasized towards those who betrayed the “plan of eternal love of God”. God’s love, in the act of salvation brought by Jesus Christ (“the most personal personality”), is always ready to renew the gift of love in the man. On the other hand, man’s answer should be full of gratitude for “new life” and the renewal of love. It should abound with with acts of mercy towards those who need love, crushed by the burden of “their way”. This way Sawicki sketches the providential plan of the eternal love of God who uses its power to solve the problem of evil and suffering.